p53 gene deletion predicts for poor survival and non-response to therapy with purine analogs in chronic B-cell leukemias - Döhner, Hartmut; Döhner, Konstanze; Bentz, Martin; Hansen, Katrin; Benner, Axel; Cabot, Georges-Philippe; Diehl, Daniela; Schlenk, Richard Friedrich; Coy, Johannes F.; Stilgenbauer, Stephan; Volkmann, Martin; Galle, Peter R.; et al. (Blood, 1995)
Conventional cytogenetic analysis in B-cell chronic lymphocytic leukemia (B-CLL) has been very difficult, and the prognostic significance of specific chromosome aberrations is under discussion. Recent improvements in fluorescence in situ hybridization (ISH) techniques have provided an alternative approach for the detection of chromosome aberrations. Here, an interphase cytogenetic study was performed to analyze the incidence and prognostic significance of a p53 gene deletion in B-CLL and related disorders. We studied mononuclear cells from 100 patients with chronic B-cell leukemias [B-CLL, 90 patients; B-prolymphocytic leukemia (B-PLL), 7; Waldenstrom's macroglobulinemia (WM), 3] by fluorescence ISH with a genomic p53 DNA probe. In a subset of patients, additional G-banding analysis and single strand conformation polymorphism (SSCP) analysis was performed. Seventeen of the 100 patients [17%; B-CLL, 11 of 90 (12%); WM, 1 of 3; B-PLL, 5 of 7] exhibited a monoallelic p53 gene deletion by ISH. G- banding analysis demonstrated abnormalities of chromosome 17 in 13 of these 17 patients, all leading to loss of band 17p13. SSCP analysis showed aberrant bands in 9 of 14 patients with a p53 gene deletion. None of 12 patients with a p53 gene deletion compared with 20 of 36 patients (56%) without a deletion responded to therapy with fludarabine or pentostatin (P < .001). The difference in survival probabilities from the time of diagnosis and from the start of treatment with purine analogs between the two groups was highly significant (P < .001). In multivariate analysis, p53 gene deletion was the strongest prognostic factor for survival. In conclusion, p53 gene deletion predicts for non- response to therapy with purine analogs and for poor survival in chronic B-cell leukemias.
Gesehen am 07.11.2024